Evaluasi Efektivitas Mesin Kiln dengan Penerapan Total Productive Maintenance pada Pabrik II/III PT Semen Padang - Andita Rahayu (The Industrial Engineering Department of Engineering Faculty at Universitas Andalas, 2014)
PT Semen Padang is a company that produces cement and it can not be separated from issues related to the effectiveness of the machinery/ equipment caused by factors such as six big losses. It can be indicated from the frequency of damage caused to machinery/ equipment because of the damage so that production targets are not achieved. Another result of damage caused by machinery/ equipment is the quality of products where the products are not meet the quality standards. Therefore, it is necessary to measure effective and efficient in the maintenance of machinery/equipment int term of solving such problems. TPM is a method which developed in Japan that can be applied to improve the productivity and efficiency of production. The applied method is one of useful methods to mantain machinery/equipment utilization including, losses that called by the six big losses. One goal of TPM is to increase the effectiveness to improve function and performance of machinery/ equipment used and reduce the six big losses contained in the machine/ equipment. Study has been conductedin W1 and W2 Kiln engine on Indarung Factory II / III PT Semen Padang. The first stage is measuring the effectiveness of W1 and W2 Kiln machine using OEE method. Furthermore, we are y measure OEE Six Big Losses and another losses that lead to the low efficiency of the Kiln machine. The data has been collected based on year 2013. Result showed that the value of OEE in W1 kiln ranged from 49% to 96%. While the value of OEE in W2 kiln ranged from 60% to 98% . It is related to the level of availability W1 kiln (average 92%) were also quite low when it is compared to the level of availability W2 kiln (average 94%) due to the length of time the kiln W1 engine damage. Refer to the value of the performance rate W1 and W2 kiln, it can be concluded that the average value of both engine performance rate is almost the same, ranging between 91% and 92%. Analysis of OEE Six Big Lossesshowed that cause of low OEE on kiln machine is breakdown loss. It also affected the reduced speed loss.